1996
DOI: 10.1016/s0928-8244(96)00096-x
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of endogenous cytokines in host resistance against an intragastric infection with Listeria monocytogenes in mice

Abstract: It has been demonstrated that endogenous cytokines including gamma-interferon (IFN-gamma), tumour necrosis factor-alpha (TNF-alpha), and interleukin-6 (IL-6) play a protective role but that IL-4 plays a detrimental role in systemic Listeria monocytogenes infection in mice. The diverse roles of IL-10 have been reported in antilisterial resistance. In this paper, we studied the role of endogenous cytokines in host resistance against an intragastric infection with L. monocytogenes in mice. The expression of cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
(21 reference statements)
2
13
1
Order By: Relevance
“…Hybridoma cell lines secreting mAbs against mouse IFN-Q (R4-6A2; IgG1), mouse TNF-K (MP6-XT22.11; rat IgG1), mouse IL-4 (11B11, rat IgG1), mouse IL-6 (MP5-20F3.11; rat IgG1) and mouse IL-10 (JES5-2A5, rat IgG1) were used [34]. The mAbs found in the ascites £uid were partially puri¢ed by (NH R ) P SO R precipitation.…”
Section: In Vivo Depletion Of Endogenous Cytokinesmentioning
confidence: 99%
“…Hybridoma cell lines secreting mAbs against mouse IFN-Q (R4-6A2; IgG1), mouse TNF-K (MP6-XT22.11; rat IgG1), mouse IL-4 (11B11, rat IgG1), mouse IL-6 (MP5-20F3.11; rat IgG1) and mouse IL-10 (JES5-2A5, rat IgG1) were used [34]. The mAbs found in the ascites £uid were partially puri¢ed by (NH R ) P SO R precipitation.…”
Section: In Vivo Depletion Of Endogenous Cytokinesmentioning
confidence: 99%
“…Third, cell proliferation and phorbol myristate acetate-and ionomycin-stimulated gamma interferon secretion by IELs from mdr1a Ϫ/Ϫ mice were actually greater (P Ͻ 0.05) than those by normal IELs. Because gamma interferon is essential for host response to L. monocytogenes, any cytokine changes in the present study would not be in a direction detrimental to host defense (19,20,23). Lastly, peripheral-T-cell proliferation, cytokine secretion, and cytotoxic function are unaffected by a lack of the mdr1a gene in mice (7).…”
Section: Discussionmentioning
confidence: 97%
“…Undoubtedly, there are numerous host defense mechanisms in place which interfere with the invasion of pathogenic bacteria such as L. monocytogenes (4,6,9,20). P glycoprotein appears to be one important protein at the epithelial level, most likely working in concert with these other factors to protect the host.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that IL-10 could be detrimental to the infected host. In other studies, this cytokine has been shown to enhance resistance against infection [29][30][31]. Some strains of lactobacilli induce production of interleukin 10 (IL-10) and transforming growth factor (TGF-b) that modulate the immune responses [32,33].…”
mentioning
confidence: 99%